Perubahan Pola Pergerakan Belanja Masyarakat Pasca Dibangun Pusat Perdagangan Modern di Solo Baru - Ardita Putri Usandy; Galing Yudana; Erma Fitria Rini (ARSITEKTURA, 2017)
The urban development can give rise to several problems in the urban devrlopment. The development of urban settellement  is the increasing number of people each year so that the need for infrastructure increases one of which is a modern trade center because demand of commodity and service is increase. But this situation is not followed by infrastructure such as modern trade center. In the beginning of  Solo Baru has built, there is no modern trade center. In progress, in 2001 there is trade center in Solo Baru. Then increased again in 2013 and 2014. In this development there are indications of changes in shopping trips of public. Based on these problems, this study aims to determine changes in shopping trip distribution of public after the establishment of modern trade center in Solo Baru in terms of spatial and aspasial trip distribution. In this study, the method used is quantitative method with 4 analytical techniques. Descriptive analysis of narrative will see how the development and characteristics of modern trade center as well as the shopping trips distribution of public in 2000 and 2015. Analysis of paired sample t test saw trip distribution changes that occurred in public spending Solo Baru in 2000 and 2015. The descriptive analysis explanatif to prove that changes in trips distribution expenditures were the result of the development of modern trade centers are supported by the deciding factor to determine the relationship of the movement, the characteristics of the trade center with the trips distribution of public. The results show that after the establishment of modern trade center in Solo there is a change ina spatial and spatial trips distribution and spatial. The trip distribution of public happens is people tend to look for a trading center strategically located in the sense that it is more accessible location with a shorter distance, with a strategic location or cause consumers will take time, and expense..Keywords: trips distribution, shopping trip, urban development